Perceraian dalam Perspektif Etika Kristen - Debi Silvia Dinata; Sepri Sepri; Sirnawati Sirnawati; Sarmauli Sarmauli (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Divorce has become an increasingly prevalent moral and social phenomenon within modern society, including among Christian communities, with profound implications for family structures, spiritual life, and the church’s testimony in the world. This study analyzes divorce from the perspective of Christian ethics, grounded in a theological and moral reflection on Matthew 19:1–12 as the biblical foundation for understanding marriage and faithfulness. The findings reveal that divorce is not merely a legal or social concern but represents a spiritual crisis and a failure to uphold the sacred covenant established by God. Contributing factors such as infidelity, domestic violence, economic pressure, and weak faith formation erode the moral values of love and fidelity. Christian ethics emphasizes love, forgiveness, and moral responsibility as fundamental principles for healing and reconciliation within broken relationships. The church is called to exercise pastoral responsibility through guidance, counseling, and restoration, fostering ethical awareness and marital integrity among believers. Thus, applying Christian ethics to the issue of divorce is essential for nurturing spiritual maturity, strengthening family unity, and preserving the moral witness of the Christian community.